The effects of different hormone treatment on endothelial function in healthy postmenopausal women. (22nd July 2013) - Akman, Levent; Duygu, Hamza; Akercan, Fuat; Ulukus, Murat; Ozerkan, Filiz; Akin, Mustafa
Abstract: We aimed to compare the effects of different types of hormone treatment (HT) on endothelial function by means of brachial artery ultrasonographic examination in postmenopausal women. Sixty-two healthy postmenopausal women were included in this study. Subjects were assigned to one of the five groups receiving 6 months of treatment [estrogen (conjugated estrogen), estrogen (conjugated estrogen) plus progesterone (medroxyprogesterone acetate; MPA), raloxifene, tibolone or control]. Endothelial function was assessed by measurement of flow-mediated dilatation (FMD) and nitrate-dependent dilatation in the brachial artery. At the end of 6 months, FMD values were found to be significantly increased in women with HT use than the control group ( p = 0.001). In subgroups, FMD increased significantly in the estrogen [12 ± 7 versus 25 ± 8, p = 0.001] and raloxifene groups [7 ± 5 versus 11 ± 3, p < 0.01] compared to tibolone and estrogen plus progesterone groups. In conclusion, endothelial function is impaired in postmenopausal women. Both estrogen and raloxifene regimens may improve endothelial functions in healthy postmenopausal women. The direct protective effects of these HT on the healthy endothelium may be more remarkable than the favorable effects on lipid profile.